The development of simulator testing for total knee replacements. Issue 2 (26th April 2021) - Maag, Chase; Metcalfe, Amber; Cracaoanu, Ioan; Wise, Casey; Auger, Daniel D.
Abstract: Professor Duncan Dowson was a pioneer in the field of tribology and simulator design. His work sparked many branches of research across orthopaedics. The first knee simulator described by Dowson was intended to measure the wear performance of early total knee replacements (TKRs). The industry has since advanced to achieve simulator designs with significant improvements including multi‐station, multi‐axis, multi‐control, and multi‐environmental capabilities. These simulators are used to test and compare not only wear, but also the kinematic/kinetic behaviour of TKRs and many other TKR design interactions prior to implantation. This has led to changes to the design of TKRs ranging from improvements to the tibial insert to the femoral component; all, in some way, thanks to Professor Duncan Dowson's inquisitive nature. This article provides a selective review to show the interdependencies of research and development endeavours starting with the evolution of knee simulators, the many advances in TKRs and finally the interconnection with cadaveric motion simulators.